Monitoramento de nidificação de Tetrapedia diversipes para avaliação histopatológica e comportamental de fêmeas expostas ao óleo de nim - Saraiva, Letícia Ferreira (Universidade Federal de São Carlos, 2025)
The solitary bee Tetrapedia diversipes Klug (1810) (Hymenoptera: Apidae) nests in pre-existing cavities and collects floral resources to build nests and feed the adult and offspring. During foraging, this native bee may come into contact with different substances applied to plants. In order to evaluate the effects of the bioinsecticide neem oil (Azadirachta indica) on the fat body cells and behavior of adult females of T. diversipes in two concentrations of the commercial formulation FitoNeem, artificial nests (trap nests) were collected from November 2023 to March 2024 and managed in the laboratory. The experimental groups of the contact exposure bioassays were: solvent control group (acetone); lowest concentration (FN-I) and highest concentration (FN-II) of Fitoneem applied in the field. Behavioral analysis of all individuals occurred at different times after exposure: time zero, 24, 48, 72 and 96 hours. Histological slides containing the fat body of 3 females for each experimental group were stained with Hematoxylin and Eosin (HE), Sudan Black, Xylidine Ponceau and PAS + bromophenol blue. In individuals exposed to Azadirachtin (FN-I and FN-II), a distinct morphological pattern of trophocytes was observed in relation to the control group, with more pronounced vacuolization in the cytoplasm and more evident nuclear granulations, while oenocytes presented clumps of nuclear chromatin compaction, atypical vacuoles in their cytoplasm and irregular nucleus. After 96 hours of exposure, a statistically significant difference was observed in the means of the individuals for speed and distance traveled, being lower in individuals exposed to higher concentrations of neem oil. There was an attempt to break diapause due to the low sample number of females. Monthly monitoring of nesting suggests that its rate during the study period, as well as mortality and parasitism rates, also influenced the low emergence of T. diversipes individuals, in addition to climatic conditions. The overall analysis of the results obtained indicates the tendency for Azadirachtin to cause sublethal effects in T. diversipes by inducing histopathological effects in fat body cells, which may affect the various functions that the organ performs, as well as the locomotion behavior of individuals.
Nesting monitoring of Tetrapedia diversipes for histopathological and behavioral evaluation of females exposed to neem oil
Keywords: Abelha Nativa; Bioinseticida; Ecotoxicologia; Video tracking; CIENCIAS BIOLOGICAS::MORFOLOGIA